Unilateral Stroke: Computer-based Assessment Uncovers Non-Lateralized and Contralesional Visuoattentive Deficits. (8th November 2021) - Villarreal, Sanna; Linnavuo, Matti; Sepponen, Raimo; Vuori, Outi; Bonato, Mario; Jokinen, Hanna; Hietanen, Marja
Abstract: Objective: Patients with unilateral stroke commonly show hemispatial neglect or milder contralesional visuoattentive deficits, but spatially non-lateralized visuoattentive deficits have also been reported. The aim of the present study was to compare spatially lateralized (i.e., contralesional) and non-lateralized (i.e., general) visuoattentive deficits in left and right hemisphere stroke patients. Method: Participants included 40 patients with chronic unilateral stroke in either the left hemisphere (LH group, n = 20) or the right hemisphere (RH group, n = 20) and 20 healthy controls. To assess the contralesional deficits, we used a traditional paper-and-pencil cancellation task (the Bells Test) and a Lateralized Targets Computer Task. To assess the non-lateralized deficits, we developed a novel large-screen (173 × 277 cm) computer method, the Ball Rain task, with moving visual stimuli and fast-paced requirements for selective attention. Results: There were no contralesional visuoattentive deficits according to the cancellation task. However, in the Lateralized Targets Computer Task, RH patients missed significantly more left-sided than right-sided targets in bilateral trials. This omission distribution differed significantly from those of the controls and LH patients. In the assessment of non-lateralized attention, RH and LH patients missed significantly more Ball Rain targets than controls in both the left and right hemifields. Conclusions: Computer-based assessment sensitively reveals various aspects of visuoattentive deficits in unilateral stroke. Patients with either right or left hemisphere stroke demonstrate non-lateralized visual inattention. In right hemisphere stroke, these symptoms can be accompanied by subtle contralesional visuoattentive deficits that have remained unnoticed in cancellation task.